Effects of 4X4 Block Scheduling - Cobb, R. Brian; Abate, Stacey; Baker, Dennis (Education Policy Analysis Archives, 1999)
The effects of a 4 X 4 block scheduling program in a middle school on a variety of student measures were investigated. These measures included standardized achievement tests in mathematics, reading, and writing, cumulative and semester grades in middle school and high school, attendance rates, and enrollment rates in advanced high school courses (in mathematics only). The block scheduling program had been in effect for four years allowing analyses of current middle and high school students who had experienced a minimum of one and one-half years of block scheduling while in middle school. The primary research design was a post-test only, matched pairs design. Students were matched on school characteristics, gender, ethnicity, grade level, and 5th grade standardized reading scores. Results were relatively consistent with the extant literature and generally positive.